KOMUNIKASI LINGKUNGAN OLEH DUTA LINGKUNGAN DALAM MELAKSANAKAN PROGRAM PELESTARIAN LINGKUNGAN “SAHABAT SUNGAI PEKANBARU” - Andriva, Africia Wulan; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Environmental Ambassador is a representation of young people who are expected to be able to become influencers in the environmental field. The 1st Runner Up of Environmental Ambassador 2018-2020 has an independent-individual work program namely the Sahabat Sungai Pekanbaru. The existence of the Environmental Ambassador program is expected to be able to assist the Department of Environment and Cleanliness (DLHK) of Pekanbaru City in overcoming problems and campaigning for the environmental love movement in Pekanbaru to the community, especially the younger generation through environmental communication. Therefore this study aims to determine the environmental communication planning of the Environmental Ambassador as a communicator in the environmental protection program "Sahabat Sungai Pekanbaru", know the implementation of the activities of the Environmental Ambassador and determine the obstacles of the Environmental Ambassador in carrying out the environmental conservation program "Sahabat Sungai Pekanbaru.”               This study uses a qualitative method with a descriptive approach with a technique to determine the research subject, namely purposive. The author uses data collection techniques through interviews, observation, and documentation. The number of informants as many as seven people according to criteria that have been determined through purposive. The data analysis technique in this study uses the Miles and Huberman Model and the data validity checking technique is the extension of participation and triangulation.               The results showed that the environmental communication carried out by the Environmental Ambassador in carrying out the environmental protection program "Sahabat Sungai Pekanbaru" carried out by the Environmental Ambassador required communication planning. The plan consists of analyzing the problem, analyzing the audience, formulating goals, developing messages, planning media production, planning management and monitoring and evaluation. In addition, the implementation of environmental communication activities from the "Sahabat Sungai Pekanbaru" is a river clean action and education to the community. And there are several obstacles encountered, such as physical barriers, semantic barriers, and social barriers. Keyword: Environmental Communication, Environment Ambassador, Sahabat Sungai Pekanbaru